1 1+(y+1)/(y-2)=(3y+1)/(y+2) Общий знаменатель (у-2)(у+2)≠0⇒y≠2,y≠-2 (y-2)(y+2)+(y+1)(y+2)=(3y+1)(y-2) y²-4+y²+2y+y+2-3y²+6y-y+2=0 -y²+8y=0 -y(y-8)=0 y=0 y=8 2 5-(2y-2)/(y+3)=(y+3)/(y-3) Общий знаменатель (y+3)(y-3)≠0⇒y≠-3,y≠3 5(y+3)(y-3)-(2y-2)(y-3)=(y+3)(y+3) 5y²-45-2y²+6y+2y-6-y²-6y-9=0 2y²+2y-60=0 y²+y-30=0 y1+y2=-1 U y1*y2=-30 y1=-6 U y2=5 3 y/(y+3)-1/(y-3)=18/(y-3)(y+3) Общий знаменатель (y-3)(y+3)≠0⇒y≠3,y≠-3 y(y-3)-(y+3)=18 y²-3y-y-3-18=0 y²-4y-21=0 y1+y2=4 U y1*y2=-21 y1=7 U y2=-3 не удов усл 4 7/(y+2)+8/(y-2)(y+2)=y/(y-2) Общий знаменатель (y-2)(y+2)≠0⇒y≠2,y≠-2 7(y-2)+8=y(y+2) y²+2y-7y+14-8=0 y²-5y+6=0 y1+y2=5 U y1*y2=6 y1=3 U y2=2 не удов усл
(x + y)³ - (x - y)³- 2y = x³ +3x²y +3xy² +y³ - ( x³ - 3x²y +3xy² - y³ ) -2y =
x³ +3x²y +3xy² +y³ - x³ + 3x²y -3xy² + y³ -2y = 6x²y +2y³ -2y = 2y(3x² +y² -1).
--- или по формуле разности кубов: (a³ - b³ =(a - b)(a² +ab+b²) .
(x + y)³ - (x -y)³ - 2y =( (x + y )- (x -y)) ( (x + y )² + (x + y )(x - y) +(x - y)² )² - 2y =
2y(x² +2xy +y² + x² - y² +x² -2xy +y²) -2y =2y(3x² +y² -1).